Toward an Integrative Framework of National Competitiveness: An application to China - Xin Li (Copenhagen Business School (CBS), 2011)
The starting point of this PhD research is two observations. The first is that people often tend to discuss a country's national competitiveness in a general tone, i.e., judging a country to be either competitive or uncompetitive, rather than making more balanced assessment, and therefore their opinions often contradict each other. The second observation is that there are many competing international reports that rank a large number of countries in terms of their national competitiveness. These reports often provide different rankings for a given country (e.g., China), and therefore the readers of these reports are often left with a confusing picture. The first observation reflects the reality that there has been a lack of commonly accepted definition of national competitiveness. The second reflects the methodological problems of the indexing-and-ranking methods commonly used by international competitiveness reports...
hdl:10398/8357
Keywords: 650